Paleomagnetic and Geochronological Results From the Zhela and Weimei Formations Lava Flows of the Eastern Tethyan Himalaya: New Insights Into the Breakup of Eastern Gondwana. Issue 1 (5th January 2019) - Bian, Weiwei; Yang, Tianshui; Ma, Yiming; Jin, Jingjie; Gao, Feng; Wang, Suo; Peng, Wenxiao; Zhang, Shihong; Wu, Huaichun; Li, Haiyan; Cao, Liwan; Shi, Yuruo
Abstract: The breakup of eastern Gondwana is among the hottest topics in the Earth sciences because of its effect on global climate during the Jurassic‐Cretaceous, its influence on the evolution of life, and its importance to paleogeographic reconstruction. To better constrain the Jurassic and Cretaceous paleogeographic position of the Tethyan Himalaya and the breakup of eastern Gondwana, a combined paleomagnetic and geochronological study was performed on the Zhela and Weimei Formations lava flows, dated at 138–135 Ma, in the Luozha area of the eastern Tethyan Himalaya. Both positive fold and reversal tests together with a maximum grouping at 100% unfolding indicate that the characteristic remanent magnetization directions are primary magnetizations acquired before folding. The tilt‐corrected directions yielded a paleopole at 0.9°N, 293.4°E with A 95 = 7.0° and a corresponding paleolatitude of 53.5°S ± 7.0°S for the Luozha sampling area (28.9°N, 91.3°E), validating that the original erupted position of the Zhela and Weimei Formations lava flows was located in the center of the Kerguelen mantle plume. Our new results, together with the published paleomagnetic, geochronological, and geochemical results, demonstrate that the Comei‐Bunbury large igneous province originated from the Kerguelen mantle plume. The temporal and spatial relationships between the Comei‐Bunbury large igneous province and the Kerguelen mantle plume indicate that eastern Gondwana initially rifted at 147 Ma and that the Indian Plate fully separated from the Australian‐Antarctic Plate before 124 Ma. Key Points: The Luozha sampling area was located at 53.5 degrees south plus‐minus 7.0 degrees south at 138‐135 Ma The Comei‐Bunbury large igneous province (LIP) originated from the Kerguelen mantle plume Eastern Gondwana initially rifted at 147 Ma, and the Indian Plate fully separated from the Australian‐Antarctic Plate before 124 Ma